Maternal Health - Abstracts of Oral Presentations (Nepal Journal of Epidemiology, 2014)
Abstracts of the Oral Presentations at the session on Maternal Health at the International Conference on Research Methodology and Research Writing (ICRMSW) 2013. DOI: http://dx.doi.org/10.3126/nje.v4i2.10174